Next-Generation Liver Medicine Using Organoid Models - Akbari, Soheil; Arslan, Nur; Senturk, Serif; Erdal, Esra (Frontiers in Cell and Developmental Biology, 2019)
“Liver medicine” refers to all diagnostic and treatment strategies of diseases and conditions that cause liver failure directly or indirectly. Despite significant advances in the field of liver medicine in recent years, improved tools are needed to efficiently define pathophysiology of liver diseases and provide effective therapeutic options to patients. Recently, organoid technology has been established as the state-of-the-art cell culture tool to study human biology in health and disease. In general, organoids are simplified three dimensional (3D) mini-organ structures that can be grown in a 3D matrix where the structural and functional aspects of real organs are efficiently recapitulated. The generation of organoids is facilitated by exogenous factors that regulate multiple signaling pathways and promote the self-renewal, proliferation, and differentiation of the cells to promote spontaneous self-organization and tissue-specific organogenesis. Newly established protocols suggest that liver-specific organoids can be derived from either pluripotent stem cells or liver specific stem/progenitor cells. Today, robust and long-term cultures of organoids with the closest physiology to in vivo liver, in terms of cellular composition and function, open a new era in studying and understanding the disease pathology as well as high-throughput drug screening. Of note, these next-generation cell culture systems carry an immense potential to be further improved by genome editing and bioengineering technologies to foster the development of patient-specific therapeutic options for clinical applications. Here, we will discuss recent advances and challenges on the generation of human liver organoids and highlight emerging concepts on their potential applications in liver medicine.